Rules for Radicals - 50 years after: https://doi.org/10.53809/2021-01-TS-n.1-67-88 ("Temas Sociais" Journal, 2021)
This article aims to (1) mark the fifty years since the publication of one of the most important works on community organization entitled “Rules for Radicals”, by Saul Alinsky; (2) leave some reflections on the relevance of this work and Alinsky's thought for social intervention today.We begin with some biographical notes about Alinsky and his path as a community organizer, we continue by presenting the book “Rules for radicals” and the rules set out in it, and end with brief reflections raised by this very controversial and pragmatic book.
Keywords: Saul Alinsky; community organization; Rules for Radicals